(untitled) (INTERNATIONAL CONFERENCE ON INTERDISCIPLINARY SCIENCE, 2024)
Inertial effects in molecular rotational Brownian motion represent a fundamental area of study in molecular dynamics and statistical mechanics. The thermal agitation of molecules results in rotational Brownian motion, which induces additional fluctuations and changes in their rotational energy. These effects have a significant impact on molecular dynamics, particularly at elevated temperatures, by altering molecular interactions and their behavior in the surrounding environment.